Combination Effect of Outdoor Activity and Screen Exposure on Risk of Preschool Myopia: Findings From Longhua Child Cohort Study - Huang, Lihua; Schmid, Katrina L.; Yin, Xiao-Na; Zhang, Jingyu; Wu, Jianbo; Yang, Guiyou; Ruan, Zeng-Liang; Jiang, Xiao-Qin; Wu, Chuan-An; Chen, Wei-Qing (Frontiers in Public Health, 2021)
Evidence regarding screen use and outdoor activity during very early childhood (i.e., from aged 1 to 3 years), and their potential combined links to the later preschool myopia is limited. This information is needed to release effective public health messages and propose intervention strategies against preschool myopia. We collected information regarding very early childhood screen use, outdoor activity and the kindergartens vision screenings of 26,611 preschoolers from Longhua Child Cohort Study by questionnaires. Logistic regression models were used to examine the association between reported outdoor activity, screen use from 1 to 3 years of age and preschool myopia. Throughout very early childhood, from 1 to 3 years, the proportion of children exposed to screens increased (from 35.8% to 68.4%, p<0.001); while the proportion of children that went outdoors ≥7 times/week (67.4% to 62.1%, p<0.001) and that went outdoors for ≥60 min/time (53.3% to 38.0%, p<0.001) declined. Exposure to fixed screen devices (adjusted odds ratio (AOR): 2.66, 95% confidence interval (CI): 2.09-3.44), mobile screen devices (AOR: 2.76, 95% CI: 2.15-3.58) and limited outdoor activity (AOR: 1.87, 95% CI: 1.42-2.51) during early childhood were associated with preschool myopia. Among children whose parents were myopic, the interactions between outdoor activity and fixed or mobile screen use on later preschool myopia were significant, the ORs and 95% CI were 3.34 (1.19-9.98) and 3.04 (1.06-9.21), respectively. Our findings suggest the possibility that the impact of screen exposure during early childhood on preschool myopia could be diminished by outdoor activity particularly for children whose parents have myopia.